A comparison of arthroscopy to ultrasonography for identification of pathology of the equine stifle. (25th February 2016) - Adrian, A. M.; Barrett, M. F.; Werpy, N. M.; Kawcak, C. E.; Chapman, P. L.; Goodrich, L. R.
Summary: Reasons for performing study: To evaluate and compare the diagnostic capability of arthroscopy and ultrasonography for the detection of pathological change in equine stifle joints. Although descriptions of the arthroscopic and ultrasonographic boundaries of the normal femorotibial joint exist, there are few examples in the literature comparing the pathological changes observed with each imaging modality. Objectives: To evaluate and compare arthroscopic and ultrasonographic examinations for characterising pathological change in the stifle joint. To describe how the results of arthroscopic and ultrasonographic examinations may differ in characterising the severity of lesions and to evaluate which lesions are best assessed with each modality. Study design: Retrospective review of ultrasonographic and arthroscopic examinations. Methods: The structures of the stifle joint were evaluated and graded for pathological change by scoring arthroscopic and ultrasonographic examinations. The presence and severity of the lesions were then compared between each modality. Results: Medial meniscal lesions were detected more often with ultrasonography than with arthroscopy. Conversely, arthroscopy was better for detection of cranial medial meniscotibial ligament (CrMMTL) tearing. Articular cartilage defects were best detected with arthroscopy and periarticular osteophytes of the medial femoral condyle with ultrasonography. Four cases had defects within one of the patellar ligaments, all of which were only characterised with ultrasonography. Conclusions: Ultrasonography and arthroscopy should be combined to best evaluate pathology of the stifle, since each modality has its own limitations depending on the location and type of lesion.